Tjatatan Mengenai Stratigraphy Pegunungan Karangbolong, Djawa Tengah - H.D. Tjia (Institute for Research and Community Services (LPPM) ITB, 1961)
The Karangbolong Mountains belong to the zone of Southern Mountains in Java. The former consists of three series rocks, the oldest being the